Corporate Culture as a Tool for Improving University's Competitiveness - Irina V. Trotsuk; Daria V. Sukhoverova (Moscow Polytechnic University, 2018)
In recent years, the terms 'corporate/organizational culture' and 'ranking' have become important reference points for the Russian system of university management and criteria for assessing the quality of higher education. However, these terms are rarely considered as interrelated, which can be explained mainly by the lack of studies assessing the role of corporate culture as a tool for improving universities' positions in the international rankings. Nevertheless, the available data allow to draw some conclusions about characteristics of the corporate culture of the leaders of the world university rankings (it is a combination of the elements of market, adhocracy and clan types of organizational culture), which are not yet typical for classical Russian universities with the dominance of the elements of clan and bureaucratic/hierarchical types of corporate culture. The article presents the results of two surveys conducted in the RUDN University on the basis of CameronQuinn methodology. They revealed the framework of competing values and showed that over the past decade the share of bureaucratic/hierarchical type decreased due to an increase in the share of market and adhocracy types of culture that are typical for the leaders of world university rankings.